Penerapan Framework PIECES untuk Analisis Kinerja Aplikasi Tumbas - Susanto, Aulia Rahmadiana (JATISI, 2025)
The utilization of information technology supports the development of e-commerce, one of which is through the Tumbas application developed by the Mojokerto District Government. The Tumbas application, developed by the Mojokerto District Government, aims to support local MSMEs by facilitating digital transactions. This study aims to analyze the performance of the Tumbas application using the PIECES (Performance, Information, Economic, Control, Efficiency, Service) framework. Data was collected through an online questionnaire to 98 respondents who are active application users. The results showed the average performance score as follows: Performance 4.07 (Good/Satisfied), Information and Data 4.04 (Good/Satisfied), Economics 4.12 (Good/Satisfied), Control and Security 3.78 (Good/Satisfied), Efficiency 4.01 (Good/Satisfied), and Service 4.11 (Good/Satisfied). Overall, the Tumbas application is considered to have good and satisfactory performance in meeting user needs. However, there is room for improvement, especially in the aspects of control and efficiency. This research provides recommendations for the development of the Tumbas application to improve service quality and support the local economy in a sustainable manner.